8=9x+6

Simple and best practice solution for 8=9x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8=9x+6 equation:


Simplifying
8 = 9x + 6

Reorder the terms:
8 = 6 + 9x

Solving
8 = 6 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
8 + -9x = 6 + 9x + -9x

Combine like terms: 9x + -9x = 0
8 + -9x = 6 + 0
8 + -9x = 6

Add '-8' to each side of the equation.
8 + -8 + -9x = 6 + -8

Combine like terms: 8 + -8 = 0
0 + -9x = 6 + -8
-9x = 6 + -8

Combine like terms: 6 + -8 = -2
-9x = -2

Divide each side by '-9'.
x = 0.2222222222

Simplifying
x = 0.2222222222

See similar equations:

| 20+-1x= | | C(x)=x^2-40x+405 | | Y-2y-3y-6=0 | | .05c=.08+7.50 | | x+5=5x+25 | | y-(-5)=-6(x-1) | | 2x-71.50=4308.50 | | x+(x+5)+(2x+11)=180 | | 3/4y-6=0 | | x-20+x= | | 695=13(k+5)+32 | | logx=0.45 | | 7b=85 | | 10(g-836)=740 | | 5x-5(-6-2x)=0 | | 5-7x=2x+8 | | 2-2y-3y=0 | | 9x-(3x+3)=4x-49 | | -2=6-x | | 29=2+3g | | 8(4w+9)=-8 | | 4x^2-11x+15=0 | | 9r+8s-5(8r-5s)= | | 3x^2+12x-24=-26 | | 1/3x^2-1/12x-1/6=0 | | 803=792-b | | -6(q-81)=-30 | | 4.3(4+2x)-4.2=13 | | 2(8x+4)=22x | | -10(s+5)=-101 | | Ln(5/x)=-2 | | k^2-4k-2=0 |

Equations solver categories